Frequently asked questions in IFRS - Collings, Steve (Chichester : John Wiley, 2013)
Provides answers to some of the most commonly asked questions on the International Financial Reporting Standards (IFRS). Covering the often complicated areas of accounting for financial instruments, tangible and intangible assets, provisions, and revenue recognition, this text also contains an overview of the standards and the thinking behind them.
1. What is the role of the International Accounting Standards Board (IASB)? -- 2. Frequently asked questions -- 3. Test your knowledge -- 4. Answers -- 5. Additional recommended reading.
Includes index.
Print version record.
Keywords: Accounting -- Standards; Financial statements -- Standards; International business enterprises -- Accounting; BUSINESS & ECONOMICS -- Accounting -- Financial; Accounting -- Standards; Financial statements -- Standards; International business enterprises -- Accounting; Electronic books; Electronic books